Distributed multi-agent communication system based on dynamic ontology mapping. (1st January 2013) - El-Ghamrawy, Sally M.; El-Desouky, Ali I.
Communication is the most important feature for meaningful interaction among agents in distributed multi-agent systems. Communication enables agent's interaction to achieve their goals. Agent communication languages provide a standard in the protocol and language used in the communication, but cannot provide a standard in ontology, because ontology depends on the subject and concept of the communication. This lack of standardisation is known as interoperability problem. In order to obtain semantic interoperability, agents need to agree on the basis of different ontologies. In this paper, a communication layer is proposed to outline the communication between agents, multiplatform communication system (MPCS) architecture is proposed to provide a highly flexible and scalable system. In addition a dynamic ontology mapping system for agent communication (DOMAC) is proposed based on different mapping approaches.